Difficulties associated with the structural analysis of proteins susceptible to form aggregates: The case of Tau protein as a biomarker of Alzheimer's disease - Hromadkova, Lenka; Kupcik, Rudolf; Jankovicova, Barbora; Rousar, Tomas; Ripova, Daniela; Bilkova, Zuzana (Journal of separation science, 2016)
Mass spectrometry coupled with bioaffinity separation techniques is considered a powerful tool for studying protein interactions. This work is focused on epitope analysis of tau protein, which contains two VQIXXK aggregation motifs regarded as crucial elements in the formation of paired helical filaments, the main pathological characteristics of Alzheimer's disease. To identify major immunogenic structures, the epitope extraction technique utilizing protein fragmentation and magnetic microparticles functionalized with specific antibodies was applied. However, the natural adhesiveness of some newly generated peptide fragments devalued the experimental results. Beside presumed peptide fragment specific to applied monoclonal anti-tau antibodies, the epitope extraction repeatedly revealed inter alia tryptic fragment 299-HVPGGGSVQIVYKPVDLSK-317 containing the fibril-forming motif 306-VQIVYK-311. The tryptic fragment pro-aggregation and hydrophobic properties that might contribute to adsorption phenomenon were examined by Thioflavin S and reversed-phase chromatography. Several conventional approaches to reduce the non-specific fragment sorption onto the magnetic particle surface were performed, however with no effect. To avoid methodological complications, we introduced an innovative approach based on altered proteolytic digestion. Simultaneous fragmentation of tau protein by two immobilized proteases differing in the cleavage specificity (TPCK-trypsin and α-chymotrypsin) led to the disruption of motif responsible for undesirable adhesiveness and enabled us to obtain undistorted structural data.
Keywords: tau Proteins; Mass Spectrometry; trypsin; biologické markery; Epitopes; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; adhezivita; Adsorption; Antibodies, Monoclonal; epitopy; lidé; Chymotrypsin; chymotrypsin; Proteolysis; magnetismus; aminokyselinové motivy; Alzheimer Disease; Trypsin; Thiazoles; Biomarkers; Magnetics; Humans; Amino Acid Motifs; proteiny tau; thiazoly; Adhesiveness; proteolýza; Alzheimerova nemoc; spektrometrie hmotnostní - ionizace laserem za účasti matrice; adsorpce; hmotnostní spektrometrie; monoklonální protilátky